2010
DOI: 10.1159/000321329
|View full text |Cite
|
Sign up to set email alerts
|

Are Bacterial Growth and/or Chemotaxis Increased by Filler Injections? Implications for the Pathogenesis and Treatment of Filler-Related Granulomas

Abstract: Background: As microbial agents have been associated with late adverse effects related to fillers antibiotic treatment has been envisaged. Objective: To determine whether biomaterials favor bacterial growth and/or attract bacteria. Methods: Hyaluronic acid, semi-permanent fillers, such as calcium hydroxylapatite, and permanent fillers, such as polyalkylimide/polyacrylamide, were used. Experiments were performed with Escherichia coli, strain HVH-U47. Bacteria were transferred to Sven-Gard agar to test mobility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…corticosteroids can be also used due to their ability to control granulomatous reactions (Sanchis-Bielsa et al, 2009). Based on the association of late reactions to cosmetic fillers with infections, suggesting that bacteria and viruses might be involved in this process, some authors had suggested the use of antibiotic therapy (Christensen et al, 2005), but this does not represent a consensus and should not be a mandatory treatment (Alijotas-Reig and Garcia-Gimenez, 2008;Alijotas-Reig et al, 2010;Alijotas-Reig and Garcia-Gimenez, 2011). Surgical excision should be the last option, since foreign body granulomas extend in finger-shaped growth within the surrounding tissues ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…corticosteroids can be also used due to their ability to control granulomatous reactions (Sanchis-Bielsa et al, 2009). Based on the association of late reactions to cosmetic fillers with infections, suggesting that bacteria and viruses might be involved in this process, some authors had suggested the use of antibiotic therapy (Christensen et al, 2005), but this does not represent a consensus and should not be a mandatory treatment (Alijotas-Reig and Garcia-Gimenez, 2008;Alijotas-Reig et al, 2010;Alijotas-Reig and Garcia-Gimenez, 2011). Surgical excision should be the last option, since foreign body granulomas extend in finger-shaped growth within the surrounding tissues ).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their wide use all over the world, the medical literature is full of reports and discussions of complications after the use of cosmetic fillers (Lemperle et al, 2004;Christensen et al, 2005;Lemperle et al, 2006;Anastassov et al, 2008;Alijotas-Reig and Garcia-Gimenez, 2008;Alijotas-Reig et al, 2010;Lemperle et al, 2010). More recently, dental journals have carried such reports in order to help surgeons, general dentists and oral pathologists to come to a correct diagnosis (Lombardi et al, 2004;Da Costa Miguel et al, 2009;Jham et al, 2009;SanchisBielsa et al, 2009;Mandel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 Especially with regard to the latter, hyaluronic acid has been used for drug delivery and therefore it has become of key importance to understand its relationship to pathogens and to study its effect on inflammatory mediators, the immune system, and markers of oxidative stress. For instance, hyaluronic acid has been used to transport chemotherapeutic drugs.…”
Section: Hyaluronic Acid and Nanomedicinementioning
confidence: 99%
“…On the other hand, HA filler did not show chemoattractive properties or stimulate bacterial growth in experimental settings. 74 Further studies are needed to better understand the mechanism leading to granuloma formation.…”
Section: Delayed Adverse Reactionsmentioning
confidence: 99%